The Rural Environment, Technology and Organic Production - Zabala Salazar, Hernando (Cooperativismo & Desarrollo, 2014)
The Colombian conflict —or in other words the leading actions of armed groups based in areas withlittle state presence— can largely be explained by the low level of agricultural development in the coun-try, and the inability to make agrarian reform a reality. Added to this is the impact that the country’stransformation has had on rural areas. It is clear that the restructuring of the rural economy must be asocial and regional transformation that puts an end to the enormous delay which has kept Colombia’srural population living in conditions of the late 19 th century. It is therefore critical to provide a holisticsolution to these situations and formulate public policy that promotes the democratization of property,association-based production, the generation of added value to traditional rural products, productionfor food self-sufficiency in the country, access to markets, improvement to family income and the chancefor the rural population to experience a fuller enjoyment of life.
Keywords: associativity; local development; organic production; rural areas; agricultural technology